Analisis Kreativitas Siswa dalam Mata Pelajaran Akuntansi pada Siswa Kelas XI IPS 1 SMA Kristen Trana Kecamatan TNS - Pemasela, Maslury; Tomasoa, George Richard; Tomasoa, Theodora Florence (Jurnal Pendidikan Ekonomi, 2023)
This study aims to analyze the level of student creativity in accounting subjects among Grade XI IPS 1 students at SMA Kristen Trana, TNS District, Central Maluku Regency. Creativity is a crucial aspect in accounting learning, as it encourages students to think critically, find innovative solutions, and develop a deeper understanding of concepts. The research employed a descriptive qualitative method, using observation, interviews, and documentation as data collection tools. The results indicate that student creativity ranges from moderate to high. This is evident in their ability to generate ideas, solve accounting case studies, and present financial reports using varied and engaging formats. Several factors support student creativity, including the use of project-based learning, teacher encouragement for exploration, and students’ intrinsic motivation. However, limitations such as restricted access to technology and interactive learning resources hinder the full development of students' potential. The study recommends innovating accounting instructional strategies to better foster creativity and improving school facilities to support a more creative and productive learning environment.